2011
DOI: 10.1371/journal.pone.0017861
|View full text |Cite
|
Sign up to set email alerts
|

Serotype Distribution and Invasive Potential of Group B Streptococcus Isolates Causing Disease in Infants and Colonizing Maternal-Newborn Dyads

Abstract: BackgroundSerotype-specific polysaccharide based group B streptococcus (GBS) vaccines are being developed. An understanding of the serotype epidemiology associated with maternal colonization and invasive disease in infants is necessary to determine the potential coverage of serotype-specific GBS vaccines.MethodsColonizing GBS isolates were identified by vaginal swabbing of mothers during active labor and from skin of their newborns post-delivery. Invasive GBS isolates from infants were identified through labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
84
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 34 publications
11
84
3
2
Order By: Relevance
“…This can be attributed to the stable relationship between serotype and pilus island combinations, and suggests that the difference in pilus island distribution between colonizing and invasive disease isolates was due to the difference in the relative invasive potential of different serotypes (Madzivhandila et al, 2011). This is similar to what has been reported by Margarit et al (2009) where it was shown that the relationship between pilus island and serotype was conserved irrespective of whether isolates were from a colonizing or invasive group.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This can be attributed to the stable relationship between serotype and pilus island combinations, and suggests that the difference in pilus island distribution between colonizing and invasive disease isolates was due to the difference in the relative invasive potential of different serotypes (Madzivhandila et al, 2011). This is similar to what has been reported by Margarit et al (2009) where it was shown that the relationship between pilus island and serotype was conserved irrespective of whether isolates were from a colonizing or invasive group.…”
Section: Discussionsupporting
confidence: 83%
“…All the isolates had been archived in skim milk, tryptone, glycerol and glucose broth (STGG) at 270 uC at the Respiratory and Meningeal Pathogens Research Unit (RMPRU), Johannesburg, South Africa. Serotyping of the isolates was determined as described previously (Madzivhandila et al, 2011). GBS reference strains 2603 V/R (PI-1 and PI-2a) and COH1 (PI-2b) were obtained from the American Type Culture Collection (ATCC).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple surveillance studies have indicated that all serotypes are able to colonize the vagina and perianal region of pregnant women, but five serotypes (Ia, Ib, II, III, and V) are predominant and are also the most frequent in human infections (8)(9)(10)(11)(12). In particular, serotype III accounts for 30 to 76% of neonatal disease cases (13,14).…”
mentioning
confidence: 99%
“…The incidence rate of GBS in the genital tract of pregnant women varies from 5 to 40% in different geographical locations (Madzivhandila et al, 2011). GBS colonization in genital system causes unpleasant repercussions and complication such as preterm labor, preterm rupture of membrane, clinical chorioamnionitis, subclinical chorioamnionitis, endometriosis, and many other post labor and neonatal infection, at the time of delivery for both mother and infant (Behrman et al, 2004;Faxelius et al, 1988;James et al, 2005).…”
Section: Discussionmentioning
confidence: 99%